Independence of the Tax Court in the Constitution of the Indonesian Republic - Anggraeni, RR Dewi (UIN JAKARTA, 2023)
This article discusses the Tax Court's independence in relation to the Constitution of the Republic of Indonesia. In order to maintain its independence, the Tax Court faces complex obstacles, such as political interference and limited resources. The purpose of this study is to analyze the implications of Article 24 Paragraph (1) of the NRI Constitution on the Tax Court's independence, as well as the Tax Court's function and authority in maintaining its independence. To obtain a comprehensive understanding of these issues, the research method employs a qualitative strategy that combines literature studies and legislative analysis. The research findings indicate that Article 24 Paragraph 1 of the NRI Constitution provides a solid constitutional basis for the Tax Court's independence. However, political interference and limited resources continue to be obstacles to implementation. Through its function and authority, the Tax Court has a significant obligation to maintain its independence by ensuring a fair, transparent, and objective trial process. This article concludes by emphasizing the significance of the Tax Court as an autonomous institution in maintaining justice in the Indonesian tax system.